Genocides in the European politics of History - Čepaitienė, Rasa (Genocidas ir rezistencija, 2024)
The concepts of “genocide” and “crimes against humanity”, which crystallised in Western legal and intellectual discourse in the 1960s, have been actively exploited in various domestic political struggles and international relations (the most prominent examples being the Holocaust and the Ukrainian Holodomor), and this has implications for the politics of history. The last 20 years have witnessed significant changes in the European Union’s historical politics, both in the EU’s enlargement to the East and in the EU’s own role in the world. Whereas the narrative that emerged in West Germany in the 1970s and 1980s and was consolidated in the EU in the 1980s and 1990s centred on the Holocaust as an event unique in world history in terms of its scale and consequences, with the wave of EU enlargement in 2004 it was challenged by the new EU members. The latter proposed to treat Nazi and Soviet totalitarianism equally, thus equating the Gulag with the Holocaust. This has made European historical politics more complicated and more susceptible to internal disagreements and misunderstandings between members. The aim of this article is to elaborate on the legal and political exploitation of the concept of ‘genocide’ in the intellectual discourse of the emerging European Community, and to identify the challenges posed to it by the new geopolitical circumstances, ranging from the collapse of the Soviet Union to the military invasion of Ukraine by Russia in 2022. Finally, the recent challenges posed by post-colonial and human rights discourses are discussed in more detail, disrupting the established politics of European history, even in Germany itself, which has been at the forefront of their formation and global implementation. The conclusion is that, despite attempts to find points of contact and compromise between these different models of memory, a consensus that satisfies everyone is unfortunately not currently possible, and is unlikely to ever be achieved.
Keywords: politics of history; Holocaust; Gulag; decolonisation; human rights